'Dangerous Dogs': Different Dog, Same Lamppost?*. (February 2016) - Bleasdale-Hill, Lydia; Dickinson, Jill
Legislation governing the regulation of dangerous dogs is notoriously fraught with difficulties, in particular concerning the definitions incorporated within, and the enforcement and application of, the relevant provisions. This paper examines two aspects of the legislative framework; the regulation of 'type-specific' breeds of dogs, and the extension of regulations relating to the control of dogs from public to private spheres. These aspects afford an opportunity for two principal justifications in favour of controlling owners and their dogs to be analysed: the protection of the public and the need to responsibilise dog owners. This paper considers the extent to which type-specific provisions and the extension of dangerous dogs legislation to cover private spheres achieve those desired aims and concludes that these goals are not clearly met. The authors recommend a consolidated piece of legislation, alongside a more sophisticated approach (supported by further research) being adopted with respect to the nature of dog ownership.